NASIR: PUJUANG MEMPERTAHANKAN KEMERDEKAAN RI DARI PADANG TAHUN 1945-1949 - Dinata, Afrijal Riko (Pendidikan Sejarah, 2014)
This thesis is a study of thematic biography by choosing a character Nasir as the research object. Strunggle of Nasir (1945-1949) worthy to investigating so, the formulation of the problem is how the role of Nasir in the fight for the Padang city. This study aimed to describe the background of life and efforts of Nasir strunggle in the Padang city during 1945-1949. In this study using the historical method perfomed by several stages. The first stage is, heuristic are through interviews , documents, and literature By studies conducted interviews with Nasir and his nearby. Literature study authors obtained from books or thesis related with him. The second stage of nsource criticism is to do the testing data through the external and internal criticism. The third stage of the analysis , a systematic and interpretation . The last stage is the writing of research reports, based on the result obtained that Nasir was born May 1925 in Pauh V freom a simple family and educated at Sekolah Rakyat (SR) , then be continue by joining with Lasykar Hizbullah . Nasir role in several battles in some areas such as areas Pauh V , In the Lubuk Kilangn areas , in the Taluk Kabung areas , and in Batu Busuk Kuranji areas. His strunggle in those areas carried aout a result , the Dutch withdrawn by the Dutch goverment to reduce criticism of local security.